IoT Based Fire Detection System for Peat Soil - Wong, Shang Le (Progress in Engineering Application and Technology, 2022)
In modern times, the development of IoT technology is faster and more advanced. Fire detection systems also inverted with IoT technology to replace traditional Fire detection systems. Users can get real-time information through the system. So, users can get notification from the system at any time or anywhere. In this project, the microcontroller used is a Raspberry Pi 4. The installation of this fire detection system is implemented to get the information’s of the surrounding peat soil.  The purpose of this microcontroller is to read data from sensors and communicate with websites and users. The fire detection sensor module, temperature and humidity sensor, and smoke detection sensor are the main sensors in this system. Users can easily view data parameters based on cloud services. User can also find out the conditions around the system in real time such as temperature, humidity and carbon monoxide concentration. The data will always be updated and displayed in the chart to give users can see the data easily. To improve the fire detection process, the Blynk application was implemented to improve the fire detection system. By using this application, users can get notification from this system in order to know the surrounding environment of the system.